Effect Investment and Land Area to Production Palm Oil Pasca Covid-19 Pandemic - RETNO FEBRIYASTUTI WIDYAWATI; FREDERICHO MEGO SUNDORO (INTERNATIONAL CONFERENCE OF ECONOMICS AND BUSINESS, 2025)
Palm oil production contributes to Indonesia’s GDP. As the world’s largest producer of palm oil, Indonesia naturally has a market for marketing this palm oil both domestically and internationally. The purpose of this study is to examine the impact of investment and land area on palm oil production in the seven provinces that produce the most palm oil in Indonesia. With panel data, multiplier linear regression was uses. From 2015-2021, the seven provinces are: North Sumatera, West Sumatera, Riau, South Sumatera, Central Kalimantan, West Kalimantan, and East Kalimantan. Eviews 9 is being used to analyze panel data. The findings indicate that investment has a positive but insignificant impact on palm production in North Sumatera, West Sumatera, Riau, South Sumatera, Central Kalimantan, West Kalimantan, and East Kalimantan from 2015 to 2021. Between 2015 and 2021, the area has a positive and significant impact on palm oil production North Sumatera, West Sumatera, Riau, South Sumatera, Central Kalimantan, West Kalimantan, and East Kalimantan. The findings of this study are new, because palm oil production can contribute to economic growth and recovery during the Covid-19 pandemic. This study is also new in that it was conducted from 2015-2021 with the seven largest CPO producing provinces in Indonesia.